ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN CASH HOLDING PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Afif, Saleh; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2016)
This research aims to analyze and provide empirical evidence related to the effect of firm size (SIZE), leverage (LEV), cash flow (CF), net working capital (NWC), and Dividend Payment (DPR) to cash holding (CHD) manufacture companies listed on the Indonesia Stock Exchange in 2010 – 2014. This research uses secondary data collected from the Indonesian Stock Exchange (IDX). The data used in the form of financial statement data manufacture company from 2010 – 2014. Of the 144 manufacture company, acquired 83 companies sampled in this study. Data were analyzed using multiple linear regression analysis. Based on the results of hypothesis testing through the F test, indicating that the variable SIZE, LEV, CF, NWC, and DPR simultaneous effect on CHD. Then through the t test showed that the SIZE, CF, and DPR variable have significant positive effect on CHD. LEV variable have significant negative effect on CHD. NWC variable has negative but not significant effect on CHD.